Unconscious Bullying in the Workplace: A Qualitative Exploration - Shivani Jandhyala; Navin Kumar (Human Research in Rehabilitation, 2024)
Bullying is an intimidating behavior that can be internalized as a learned behavior. The Study aimed to create thoughtfulness among employees about how and what makes an individual become a bully or engage in bullying with no awareness. The Study explored the view of an employee to understand how unconscious behavior can influence one’s actions and behavior toward bullying. This Study practiced a Focus Group Discussion and conducted the discussion virtually on a sample of 31 employees of the Service and Non-Service sectors. The researcher discussed with 11 participants in one group and 20 in another on two different days. This discussion helped to provide awareness about unconsciousness in bullying behavior at the workplace. This discussion helped to gather views of working people from various sectors. It illustrated that focus groups could enhance awareness and empower one’s thoughts and beliefs. An important finding can be that the group identified the challenges of Unconscious bullying, like lack of self-awareness, marginal ethical and moral guidance, and eminence. In conclusion, it is observed from the discussion and responses from employees that there is a need to have healthy communication abilities in stating their feelings assertively.